Large-scale scientific computing : 11th International Conference, LSSC 2017, Sozopol, Bulgaria, June 5-9, 2017, revised selected papers /: 11th International Conference, LSSC 2017, Sozopol, Bulgaria, June 5-9, 2017, revised selected papers. (2018) - Unknown
No abstract available